A Homoploid Hybrid Between Wild Vigna Species Found in a Limestone Karst - Takahashi, Yu; Iseki, Kohtaro; Kitazawa, Kumiko; Muto, Chiaki; Somta, Prakit; Irie, Kenji; Naito, Ken; Tomooka, Norihiko (Frontiers in Plant Science, 2015)
Genus Vigna comprise several domesticated species including cowpea and mungbean, and diverse wild species. We found an introgressive hybrid population derived from two wild species, V. umbellata and V. exilis, in Ratchaburi district, Thailand. The hybrid was morphologically similar to V. umbellata but habituated in a limestone rock mountain, which is usually dominated by V. exilis. Analyzing simple sequence repeat loci indicated the hybrid has undergone at least one round of backcross by V. umbellata. We found the hybrid acquired vigorous growth from V. umbellata and drought tolerance plus early flowering from V. exilis, and thus has taken over some habitats of V. exilis in limestone karsts. Given the wide crossability of V. umbellata, the hybrid can be a valuable genetic resource to improve drought tolerance of some domesticated species.